Vascular e-Learning in the MENA Region during the COVID-19 Pandemic - Nikolaos Patelis; Sean Matheiken; Theodosios Bisdas; Zaiping Jing; Jiaxuan Feng; Matthias Trenner; Paulo Eduardo Ocke Reis; Stephane Elkouri; Alexandre Lecis; Dirk Le Roux; Mihai Ionac; Marton Berczeli; et al. (Dubai Medical Journal)
Introduction: With the steady rise in interest in e-learning and the sudden boost provoked by the COVID-19 pandemic, it becomes necessary to explore the e-learning experience within the medical community in the MENA region. Methods: An online survey was conducted during the early phase of the COVID-19 pandemic (June 15 – October 15, 2020). Results: Seventy-eight vascular surgeons and trainees from 16 countries participated. 88% of the participants were male. 55% attended more than 4 activities. More than half of the activities did not lead to any official certification. Topic was the primary determinant for attending an activity. National societies and social media played a major role in disseminating activity-related information. Lack of time, increased workload, differences in time zone, and technical issues were the main obstacles cited. 84.7% of the participants had a positive impression. Conclusion: As the COVID-19 pandemic boosted e-learning activities in vascular surgery, a shift was observed in the learning mode and new leadership skills were called upon. Novel ways of quality control are required.